Rancang Bangun Game Edukasi Visual Novel Kisah Pangeran Diponegoro dan Pengaruhnya Terhadap Minat Belajar Siswa - Suryadana, Anly; Deli, Deli (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
This research was conducted to develop a visual novel learning media titled "Kisah Pangeran Diponegoro" using the ADDIE development approach. This study is used to analyze the influence of using the visual novel learning media on students' learning interest through quantitative research methods. Data on students' learning interest after playing the game will be collected through questionnaires and analyzed. Afterwards, it can be proven that Performance Expectancy (PE) and Hedonic Motivation (HM) did not have impact on students’ Behavior Intention (BI) because the sig value (2-tailed) is greater than the significance level, i.e., 0.950 > 0.05. On the other hand, Students' Innovativeness, Learning Value, Effort Expectancy, Facilitating Conditions and Social Influence have a significant impact on students’ Behavior Intention (BI) because the sig value (2-tailed) is lower than the significance level, i.e., 0.001 < 0.05.